Analisis Vegetasi Gulma Dan Jenis Serangga hama Pada Pertanaman Padi Serta Sayuran Di Kabupaten Nabire Provinsi Papua - Gobai , Lusia; Purnomo, Dwiana Wasgito; Noya, Alce Ilona; Purbokurniawan (Program Pascasarjana Universitas Papua, 2024)
ABSTRACT : The study of weed vegetation analysis and types of insect pests in rice and vegetable plantations has been conducted in SP1 and Wadio village, Nabire Regency. The study aims to analyze the types of weeds found in rice and vegetable plantations. This study used transect method per plot. Plots were made as many as 50 plots each with a size of 2 m x 2 m. The results showed that the weed vegetation of vegetable plantations in Wadio and SP1 Villages, obtained 21 families 31 species. Weeds in rice plantations consisted of 9 families and 13 species with a total of 786 individuals, while in vegetable plantations consisted of 12 families and 17 species, so that the total is 836 individuals. The Sorensen similarity index of weeds obtained for both rice and vegetable plantations varied with a range between very high 100%, high range 66.66 and low range 28.57. The insect pest similarity index in both fields varied with a range between 66.66 - 100%.